Mathematical modeling of dynamics of website quality characteristics - Pasichnyk, Natalia; Dyvak, Mykola; Pasichnyk, Roman (Publishing House of Lviv Polytechnic National University, 2013)
The article offers a set of dynamic models of predicting the website attendance. The numerical experiments were conducted to identify these models. It allowed the authors to structure an adequate model to predict overall and target attendance, basing on the analysis of the characteristics of business processes of an object represented by this website. Проаналізовано множину динамічних моделей прогнозування відвідування веб-сайтів. ідентифіковано ці моделі на підставі численних експериментів Це дало змогу структурувати адекватні моделі для прогнозування загальної та результативної відвідуваності, грунтуючись на аналізі характеристик бізнес-процесів об'єкта, який цей веб-сайт представляє.
Математичне моделювання динаміки характеристики якості веб-сайту
Keywords: website attendance; website traffic; descrete dynamic models; structure identification; prognosis properties